Amyloidosis: an unusual cause of upper gastrointestinal bleeding. (26th October 2016) - Siau, Keith; Elzubeir, Amera; Cooper, Sheldon C; Iqbal, Tariq
Abstract : We report a rare case of upper gastrointestinal bleeding in a 55-year-old man with monoclonal gammopathy of unknown significance presenting with abdominal pain, weight loss and melaena. Gastroscopy was unremarkable, but melaena persisted, with the development of symptomatic anaemia. While colonoscopy excluded a lower gastrointestinal aetiology, CT revealed jejunitis, confirmed at capsule endoscopy. Histopathological examination of specimens obtained at single balloon enteroscopy revealed an unusual aetiology: small bowel AL-amyloidosis. We review his clinical presentation, radiological, endoscopic and histological findings and review the literature of this unusual condition.